Identification of a Devernalization Inducer by Chemical Screening Approaches in Arabidopsis thaliana - Shirakawa, Makoto; Morisaki, Yukaho; Gan, Eng-Seng; Sato, Ayato; Ito, Toshiro (Frontiers in Plant Science, 2021)
Vernalization is the promotion of flowering after prolonged exposure to cold. In Arabidopsis thaliana, vernalization induces epigenetic silencing of the floral repressor gene FLOWERING LOCUS C (FLC). The repressive epigenetic mark trimethylation of lysine 27 on histone H3 proteins (H3K27me3) is a critical contributor to the epigenetic silencing of FLC. Interestingly, the deposited H3K27me3 in the FLC locus can be erased by short-term high-temperature treatment. This is referred to as devernalization. In this study, we identified a novel chemical compound, 4-Isoxazolecarboxylic acid, 3,5-dimethyl-2-(4-fluorophenyl)-4-isoxazole carboxylic acid 1-methyl-2-oxoethyl ester named as DEVERNALIZER01 (DVR01), which induces devernalization in Arabidopsis seedlings, by an FLC-luciferase reporter-based high-throughput screening assay. DVR01 decreased the amount of H3K27me3 in the FLC locus in vernalized plants, resulting in the upregulation of FLC in the whole plant, including the vasculature and meristem, where FLC represses floral induction genes. We also showed that a two-week treatment with DVR01 reverted plants with a vernalized status back to a fully nonvernalized status. Collectively, this study provides a novel structure of DVR01, which modulates devernalization via demethylation of H3K27me3 in the FLC locus.